Warning Signs of Aggression in the School Environment and the Issue of their Perception and Evaluation - Tibor A. Brecka (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This paper provides a theoretical analysis of violent behavior within school environments, synthesizing relevant literature to describe key aspects of aggression and its manifestations. It explores the challenges of perception, interpretation, and timely evaluation of warning signs, focusing on the factors that influence recognition and response to signals indicating potential risks. By presenting a comprehensive framework, this study aims to enhance theoretical understanding and offer insights into improving awareness and evaluation techniques. These findings contribute to fostering a safer and more protective school environment for students and staff.